The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1186/1471-2296-12-101
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and burden in relatives of patients with schizophrenia in a middle income country

Abstract: BackgroundMost studies of family attitudes and burden have been conducted in developed countries. Thus it is important to test the generalizability of this research in other contexts where social conditions and extended family involvement may be different. The aim of this study was to assess the relationship between the attitudes of caregivers and the burden they experience in such a context, namely Arica, a town located in the northernmost region of Chile, close to the border with Peru and Bolivia.MethodsWe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
24
3
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 70 publications
9
24
3
12
Order By: Relevance
“…Parents especially mothers were the caregivers with the highest score (CSI), this finding is consistent with (19) , this is because a large percentage of them are primary caregivers, taking responsibility for all the care of their schizophrenic son. This is due to the greater involvement of mothers, both psychologically and in practice (in their role) (20) and is an aspect that needs to be addressed more actively by mental health professionals (12,22,23) .…”
Section: Psychosocial Burden Among Caregivers Of Patients ………supporting
confidence: 75%
“…Parents especially mothers were the caregivers with the highest score (CSI), this finding is consistent with (19) , this is because a large percentage of them are primary caregivers, taking responsibility for all the care of their schizophrenic son. This is due to the greater involvement of mothers, both psychologically and in practice (in their role) (20) and is an aspect that needs to be addressed more actively by mental health professionals (12,22,23) .…”
Section: Psychosocial Burden Among Caregivers Of Patients ………supporting
confidence: 75%
“…This finding was consistent with the results of some other studies such as those of Angela-Cole and Caqueo-Urízar (10,28). This matter showed that long-term caring for a patient with psychiatric disorder at home can create tension and negative attitude in the caregivers (10). Though in the conducted research cases, females were introduced as the main caregivers, in the current study, more than half of the caregivers (52%) were male .This finding matches the Indian research based results (22).…”
Section: Discussionsupporting
confidence: 83%
“…The more the care hours per week, the more negative the attitude. This finding was consistent with the results of some other studies such as those of Angela-Cole and Caqueo-Urízar (10,28). This matter showed that long-term caring for a patient with psychiatric disorder at home can create tension and negative attitude in the caregivers (10).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations